ANTESEDENTS DARI CUSTOMER LOYALTI PADA JASA RESTORSAN - Dine Hilana Mulyani (Jurnal Manajemen dan Pemasaran Jasa, 2008)
The bald time sat, It could satisfact The obje time sr satisfacti loyalty The de# of this research applies a survey toward unit of analysis on one of famous brand full service re aurant while they waiting or having waiting listed at malls in Jakarta such Pondok lndah Mall, Plaza Indonesia and Plaza Senayan. The aggregate number of costumers being respondent of the study is 128.The reset rch finding concluded that antecedents which consist of perceived waiting time, had signifiCa effect to waiting time satisfaction and service satisfaction but positive mood and value attainme t only give moderate effect to service satisfaction and loyaltyKeyword : waiting time, costumer satisfaction, service satisfaction, loyalty, mood to loyalty and value att inment